2005
DOI: 10.3386/w11271
|View full text |Cite
|
Sign up to set email alerts
|

Betting on Death and Capital Markets in Retirement: A Shortfall Risk Analysis of Life Annuities

Abstract: Retirees must draw down their accumulated assets in an orderly fashion, so as not to exhaust their funds too soon. We compare alternative phased withdrawal strategies to a life annuity benchmark using German data; one particular phased withdrawal rule seems attractive, as it offers relatively low expected shortfall risk, good expected payouts for the retiree during his life, and some bequest potential; results are similar for the US case. Delayed annuitization may also appeal, as it offers higher expected bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Through the theory that marginal utility consumption of the "elderly" (over 65 years) is decreasing but coupled with the allocation of wealth owned in financial and health investments (Börsch-Supan & Stahl, 1991). Another study found that retirees who had excess funds preferred to delay benefit annuities in hopes of gaining more in older age (Dus et al, 2005).…”
Section: Influence Of Capital Markets Inflation and Demographics On The Growth Of Pension Fund Assets In The State Organization Of Islamimentioning
confidence: 99%
“…Through the theory that marginal utility consumption of the "elderly" (over 65 years) is decreasing but coupled with the allocation of wealth owned in financial and health investments (Börsch-Supan & Stahl, 1991). Another study found that retirees who had excess funds preferred to delay benefit annuities in hopes of gaining more in older age (Dus et al, 2005).…”
Section: Influence Of Capital Markets Inflation and Demographics On The Growth Of Pension Fund Assets In The State Organization Of Islamimentioning
confidence: 99%
“…9 This finding stands in sharp contrast to standard unit-linked insurance products and traditional drawdown strategies, in which a more aggressive portfolio strategy directly translates into higher year-on-year consumption volatility. (See, e.g., Dus, Maurer, and Mitchell (2005), Horneff, Maurer, Mitchell, and Dus (2008), and Maurer, Mitchell, Rogalla, and Kartashov (2013) for a description of these products.) only on age.…”
Section: Introductionmentioning
confidence: 99%
“…Since the underlying immediate annuity is purchased if, and only if, the investor is alive, the survival probabilities in equation (7b) must be conditioned on survival to time , and the factor   appears in the denominator of the price. Strictly speaking, the delayed payout annuity is a hybrid 5 The following researchers have analyzed the strategy of delaying the purchase of an immediate annuity: Kapur and Orszag (1999), Dushi and Webb (2004), Milevsky and Young (2003), Dus, Maurer and Mitchell (2005) and Horneff, Maurer, Mitchell, and Dus (2006). The last reference has an excellent summary of this literature.…”
Section: Delayed Purchase Annuitiesmentioning
confidence: 99%